Pengaruh Locus Of Control Internal dan Eksternal terhadap Kinerja Dimoderasi Etika Kerja Islam - Ika Aghnia Santoso; Wyati Saddewisasi; Yuli Budiarti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
Human capital management is vital in organizations for improving individual performance. Purpose: to analyze the influence of LCI and LCE on employee performance, with Islamic work ethics as a moderating variable. This study employs a quantitative approach, utilizing primary data collected through questionnaires. Sampling was conducted using purposive sampling techniques on 69 respondents. Data analysis was conducted using Structural Equation Modeling (SEM). Results: (1) LCI significantly influences employee performance, (2) LCE influences employee performance, (3) Islamic work ethics act as a moderating variable in the relationship between LCI and employee performance, but do not moderate the relationship between LCE and employee performance. Conclusion: Proper management of Islamic work ethics is an important factor in improving employee performance. This is particularly related to how individuals perceive external control (LCE) in the workplace as part of efforts to enhance productivity.